Aberfan. Lamenting Memory. Issue 1 (2nd January 2017) - Gerlach, Joe
Abstract : October 2016 marked fifty years since the unfolding of a disaster, the name of which has been burnished as a synonym for singular, unimaginable tragedy: Aberfan. On the morning of Friday 21 October 1966, in the small coal-mining village of Aberfan, Wales, a huge torrent of colliery waste amassed precariously in a vast, industrial tip, atop of a valley, gave way. Thousands of cubic meters of coal sludge liquefied and hurtled down the steep hill toward the village, engulfing Pantglas Junior School and a number of nearby houses. One hundred and forty-four died, 116 of them, children. In the ensuing recriminations and official enquiry into the catastrophe, the United Kingdom's National Coal Board was rebuked for extreme industrial negligence. Among the litany of geographical cataclysms, Aberfan was one foretold in village lore but willfully ignored by corporatist interests. As summits of memorial for the fiftieth anniversary reach their zenith, I pause here, in lament.